История России: учебник - Поляк Г. Б. Георгий Борисович; Маркова А. Н. Анна Николаевна; Квасов А. С. Александр Сергеевич; Айсина Ф. О.; Бородина С. Д.; Воскресенская Н. О. (Cogito ergo sum)
Авт. указаны на с. XV.